Comparison of acute kidney injury and renal replacement therapy in patients with rhabdomyolysis acutely intoxicated with psychotropic or chemical substances - Babulovska, Aleksandra; Velikj Stefanovska, Vesna; Chaparoska, Daniela; Simonovska, Natasha; Pereska, Zanina; Jurukov, Irena; Kostadinoski, Kristin; Naumovski, Kiril (My University, 2021)
Objective: We determine the risk factors for the development of acute kidney injury and the necessity of renal replacement ther- apy (RRT) for patients with rhabdomyolysis due to acute intoxica- tion with psychotropic and chemical substances. Methods: This was a prospective clinical study conducted from 1 January to 31 December 2019 at the University Clinic for Toxicology in Skopje. The study included patients with rhabdo- myolysis divided in to two groups in accordance with the sub- stance used for intoxication (psychotropic or chemical). Rhabdomyolysis was defined as a creatine phosphokinase (CPK) >250U/L. The diagnosis and the stages of the acute kidney injury were defined using the Kidney Disease: Improving Global Outcomes (KDIGO) classification. Data were statistically analyzed in SPSS software, version 22.0 for Windows (SPSS, Chicago, IL, USA). Results: Acute kidney injury occurred in 15% of 140 patients with rhabdomyolysis of whom 66.7% (n ¼14) had psychotropic intoxication and 33.3% had chemical intoxication (n ¼7). Statistical analysis showed significantly increased prevalence in the psychotropic group compared to those with chemical intoxi- cation (p ¼0.0002). The highest prevalence of acute kidney injury in the psychotropic intoxication group was heroin (60%) and methadone (40%), followed by neuroleptics (25%), anticonvul- sants (17.7%) and antidepressants (8.3%). In the chemical intoxi- cation group, acute kidney injury was registered in 15.9% of patients. The highest prevalence of acute kidney injury in this group was due to ethylene glycol (100%) and fungus poisoning (33.3%), followed by pesticides (20%) and corrosives (16.7%). With regards to RRT, there was a significantly higher prevalence in patients with psychotropic intoxication compared to chemical intoxication (p ¼0.0001). Patients intoxicated by psychotropic or chemical substances, with acute kidney injury and rhabdomyoly- sis had higher values for aspartate aminotransferase (AST), ala- nine aminotransferase (ALT), creatine phosphokinase (CPK), troponin and myoglobin. In the group with chemical intoxication, patients with acute kidney injury had higher values for AST (p ¼0.3277), ALT (p ¼0.9616) and troponin (p ¼0.0051) com- pared to those without acute kidney injury. The quantity/value of CPK (p ¼0.8348) and myoglobin (p ¼0.1127) was higher in patients with acute kidney injury intoxicated by chemical substances. Conclusion: The prevalence of acute kidney injury and necessity for RRT was significantly higher in psychotropic intoxication com- pared to chemical intoxication. Certain toxic agents in acutely intoxicated patients with rhabdomyolysis may have an important role in the development of acute kidney injury. Patients with acute kidney injury and rhabdomyolysis as well as those intoxi- cated with psychotropic substances have significantly higher 564 EAPCCT 2021 ABSTRACTS values for CPK, AST, ALT, troponin, and myoglobin compared to values for CPK, AST, ALT, troponin, and myoglobin compared to those without acute kidney injury.